RADIATION CHARACTERISTICS OF KHMILNYK RADON GROUNDWATER - Vyzhva, S.; Shabatura, O.; Onischuk, D.; Onischuk, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Ground waters of plutonic acid rock bodies tend to have a high radon content. Using radon-high domestic and medicinal waters could be a factor in contaminating the indoor air and increasing the background radiation levels. Effective radon therapy therefore requires an accurate assessment of radon content. Determining the correct doses of radon can only be based on a detailed study of the mechanisms of its accumulation in the groundwater, its chemical composition, pressure, temperature, hydrogeological regime, depth of water supply points, transportation time etc. Groundwater samples were taken from 5 deep wells. To make an accurate assessment of the radon content in the Khmilnyk groundwater, we conducted a series of comprehensive chemical and radiological laboratory tests, which included emanation measurements with the help of the РРА-01М-03 instrument (30% accuracy) and a series of gamma-spectrometric analyses. There were obtained data on mass content of radium-226, volume content of radon ranging from 15 to 44 MBq/m3, and the content of radon formed by dissolved and sorbed radium. Analysis of radon components showed that its accumulation in groundwater is mainly "emanational-diffusive" in nature and is hardly dependent on the chemical composition of water. No obvious correlation has been found between radon concentration and the chemical composition of the groundwater except such components as carbon dioxide, manganese, SO4 2- and Cl-. These are likely to have effect on the physics and chemistry of radium sorption. The projected dosage produced by the Khmilnyk groundwater radon was calculated from the annual equivalent doses for every water point. The results showed that a 100-hour exposure with maximum levels of radon dissolved in groundwater is likely to result in significant radiation doses (from 0.005 to 0.025 mSv per year) used in radon therapy. Groundwater from points having the highest radon levels (Well 8 and Well 12) used in radon therapy (over 100 hours per year) may result in radiation doses of 0.3-0.4 mSv per year, which is in compliance with the public health regulations. The suggested approach to identifying the physical and chemical mechanisms of groundwater radon accumulation provides an insight into its spatial and temporal variability. The research results can be used in radiological monitoring in order to ensure the safety of radon therapy and compliance with the public health regulations.